Fate of spoilage and pathogenic microorganisms in acidified cold-filled hot pepper sauces - Lobo Chinchilla, Ariela (2019)
Consumption of spicy foods and hot sauces is currently a popular trend worldwide. Shelf-stable acidified sauces are commonly hot-filled to ensure commercial sterility, but cold-fill-hold processes might also be suitable if microbial safety and stability are ensured. For this study, model acidified hot pepper sauces were developed and characterized. The effects of sauce pH and of two different organic acids on the survival of Pichia manshurica and Lactobacillus curvatus isolated from contaminated commercial hot sauces and on pathogenic Escherichia coli O157:H7, Salmonella enterica, and Listeria monocytogenes were assessed. Full factorial designs with three levels for pH (3.2, 3.5, and 3.9) and two for organic acid (citric and acetic) were used to determine the effects of these factors and their interactions on the survival of the microorganisms. Commercially sterile sauces were independently inoculated and kept at ambient temperature. Microbial counts were determined at different sampling times, depending on the treatment evaluated. Sauces acidified to pH 3.2 with citric or acetic acid were inoculated with cocktails of five strains or serotypes of the three pertinent pathogens, and inactivation curves were determined. Trials were performed in triplicate. A greater than 5-log reduction of P. manshurica and L. curvatus was achieved in less than 6 h in sauces adjusted to pH 3.2 with acetic acid. Greater than 5-log reductions of pathogenic bacteria were achieved 0.5 h after inoculation in sauces acidified to pH 3.2 with acetic acid. In contrast, at least 48 h was required to guarantee the same inactivation for the most tolerant pathogen when citric acid was used. Thus, a cold-fill-hold process may be a suitable alternative for acidified hot pepper sauces. Based on survival of the microorganisms evaluated in this study, microbial safety and stability can be achieved by adjusting the pH to 3.2 or less by the addition of acetic acid.